The 100 Top-Cited Studies on Neuropsychology: A Bibliometric Analysis - Zhang, Yang; Xiong, Ying; Cai, Yujia; Zheng, Linli; Zhang, Yonggang (Frontiers in Psychology, 2020)
Objective: The present study aimed to identify and analyze the bibliometric characteristics of the 100 top-cited studies on neuropsychology. Methods: We searched the Web of Science Core Collection database to collect studies on neuropsychology from inception to the 31st December 2019. Two authors independently screened the literature and extracted the data. Statistical analyses were performed using R software. Results: The 100 top-cited articles were cited a total of 166,123 times, ranging from 736 to 24,252 times per article. All of the studies were published from 1967 to 2014 in 47 journals. Neuropsychologia had the highest number of articles (n = 17), followed by Neurology (n = 8). The top three most productive countries were the USA (n = 60), England (n = 13), and Canada (n = 8). Eight authors contributed the same number of studies as the first author (n = 2) or corresponding author (n = 2). The most productive institute was the University of California (n = 9), followed by the University of Pennsylvania (n = 4). Of the 100 top-cited publications, 64 were original articles and 36 were reviews. The top three Web of Science categories were clinical neurology (n = 28), behavioral sciences (n = 19), and psychiatry (n = 11). Conclusions: This study provides insight into the impact of neuropsychology research, and may help doctors, researchers, and stakeholders to achieve a more comprehensive understanding of trends and most influential contributions to the field, thus promoting ideas for future investigation.